TEKS HIKAYAT CERITA NABI MUHAMMAD SALLALLAHU ‘ALAIH WA SALLAM BERNIAGA KE NEGERI SYAM DAN PERKAWINANNYA DENGAN SITI KHADIJAH: KAJIAN STRUKTUR DAN FUNGSI (The Story of the Prophet Muhammad Sallallâhu ’alaihi Wa Sallam Trading to Syam State and His Marriage with Siti Khadijah: Study of Structure and Function) - Septia, Emil (Balai Bahasa Sumatra Barat, 2015)
Abstract“The story of the Prophet Muhammad Sallallahu ‘Alaihi Wa Sallam traded to Sham state and his marriage with Siti Khadijah” was written in Arabic-Malay script with writing pattern that is not considered to be prevalent in the present. This story tells about the juorney of the prophet Muhammad Sallallâhu ’Alayhi Wa Sallam traded to the land of Sham. In each trip run trading business Prophet Muhammad procure attack, but the accident can be resolved by variety of miracles on permission and the power of Allah through the intermediary of the angels, so the Prophet Muhammad always survived with a large fortune on its trading business. Hearing the news, Khadijah was very pleased and proud of him so that she asked Prophet Muhammad to be her husband and her priest. This research is Philology, which based its work on the written materials or ancient text. The method used in this research was the transliteration and conten anlysis. Based on the data analysis it can be concluded as follows. First, results of transliteration method found the writing word from Arabic. The language used in this text is Malay, Minangkabau, and Arabic as well as some archaic words. Second, the structure of the text is rhythmic prose structure, each one stanza of poem consists of four lines and patterned rhyme /aaaa/. Character names, places, and the events are not much different from the stories of the life history of Prophet Muhammad that contained in Alquran. Third, the text of this story is a literary work of Islamic influence has several functions, they are the function of religion/propaganda, didactic/educational media, and solace.Keywords: text, tale, story, structure, functionAbstrakCerita Nabi Muhammad Sallallâhu ’Alaihi Wa Sallam Berniaga ke Negeri Syam dan Perkawinannya dengan Siti Khadijah masih ditulis dalam aksara Arab-Melayu dengan pola penulisan yang tidak dianggap lazim pada saat sekarang. Cerita ini berisikan tentang perjalanan Nabi Muhammad s.a.w. berniaga ke negeri Syam. Dalam setiap perjalanan menjalankan usahaperdagangan Nabi Muhammad s.a.w. mendapat serangan, namun musibah itu dapat diatasi dengan berbagai mu’jizat Beliau atas izin dan kuasa Allah Swt. melalui perantara para malaikat, sehingga Nabi Muhammad s.a.w. selalu selamat dengan membawa keberuntungan yang besar atas usahaperdagangannya. Mendengar kabar itu, Khadijah sangat senang dan bangga hingga ia meminta Nabi Muhammad menjadi suami dan imam baginya. Penelitian ini merupakan penelitian filologi, yang mendasarkan kerjanya pada bahan tertulis atau naskah kuno. Metode yang digunakan adalahmetode transliterasi dan analisis isi (yang ditekankan pada struktur dan fungsi). Berdasarkan analisis data dapat disimpulkan hal-hal berikut. Pertama, dari hasil transliterasi terdapat penulisan kata dari bahasa Arab. Adapun bahasa yang digunakan dalam teks ini adalah bahasa Melayu, Minangkabau, dan Arab serta terdapat beberapa kata yang arkais. Kedua, struktur yang terdapat dalam teks merupakan struktur prosa berirama, setiap satu bait syair terdiri dari 4 baris dan berpola rima /aaaa/ Nama tokoh, tempat, serta peristiwa tidak jauh berbeda dengan cerita-cerita sejarah hidup Nabi Muhammad s.a.w. yang terdapat dalam Alquran. Ketiga, teks cerita ini adalah sebagai karya sastra pengaruh Islam mengemban beberapa fungsi, yaitu fungsi religi/dakwah, didaktis/media pendidikan,dan pelipur lara.Kata Kunci: teks, hikayat, cerita, struktur, fungsi